Our ultraviolet Sun - Dwivedi B.N. (My University, 2025)
High-resolution ultraviolet observations of the Sun from SOHO and TRACE spacecraft have provided a wealth of new information on plasma temperature, density, abundance anomaly, plasma flows, turbulence, wave motions, etc. in various solar structures. We present our ultraviolet Sun that has provided some landmark new results, especially from the line-shifts and broadenings of vacuum ultraviolet spectral lines, pinpointing the physical processes that maintain the Sun's hot corona, and accelerate the fast solar wind as well as locate its source region.